Preparação e caracterização de materiais híbridos celulose/NbOPO4.nH2O a partir de celulose branqueada de bagaço de cana-de-açúcar - Pereira, Paulo H. F. [UNESP]; Voorwald, Herman Jacobus Cornelis [UNESP]; Cioffi, Maria O. H.; Pereira, Maria L. C. P. da S. (Assoc Brasil Polimeros, 2012)
This work describes the preparation and characterization of cellulose/hydrous niobium phosphate hybrid with bleached cellulose from sugarcane bagasse. The hybrid was prepared in two different forms: named methods I and II. Method I consisted in dissolving metallic niobium in a fluoridric/nitric (100:10) mixture, with aging time of 16 hours in which the sugarcane bagasse was in contact with the acid solution. Phosphoric acid was then added to the solution for precipitation of the material. Method II was similar, but metallic niobium was diluted in a fluoridric/nitric (160/100) solution without aging time. In both methods different proportions of Cel/NbOPO4 center dot nH(2)O were used: (10:10); (10:6) and (10:2). These materials were characterized by X-ray diffraction (XRD), thermogravimetry (TG/DTG) analysis and scanning electronic microscopy (SEM). The deposition of niobium phosphate and an increase in crystallinity were observed.
Preparation and Characterization of a Cellulose/NbOPO4 center dot nH(2)O Hybrid from Bleached Sugarcane Bagasse
Keywords: Sugarcane bagasse; organic-inorganic hybrid; hydrous phosphate niobium